The Relationship Between Initial Hematocrit and Base Excess For Signs Of Hemorrhagic Shock In Patients With Blunt Abdominal Trauma - Akhsan, Alfie Barkah; Usman, Nurhayat; Rudiman, Reno (Jurnal llmu Bedah Indonesia, 2017)
Introduction: Trauma abdominal and pelvic part of the largest causes of death and, if diagnosed early, the deaths could have been prevented. By increasing the capacity for early detection and prompt and appropriate action, will produce a satisfactory outcome. In patients with bleeding, hemodilution appear within a few minutes to obtain a decrease in hematocrit. BE decline is the result of pyruvic acid metabolism occurring anaerobic tissue hypoperfusion due to bleeding unresolved. There is a strong correlation between the decrease in hematocrit and BE with shock because of intra-abdominal haemorrhage. To analyze the relationship between decreased hematocrit and BE in bleeding patients we investigated the relationship between the initial value of hematocrit and BE against any signs of shock because of intra-abdominal hemorrhage in patients with blunt abdominal trauma. Methods: cross-sectional of the 34 subjects. The research data obtained from history taking, physical examination, investigation, and medical records. Conducted a comparative analysis of Kruskal-Wallis. Test for normality by Kolmogorov-Smirnov test. A p value <0.05 indicates a significant relationship between variables. Data were analyzed using SPSS version 19. Result: It was found an average increase in the pulse (P) frequency with decreasing hematocrit (Ht) is 92.67 ± 6.43x / min for group Ht> 40%, 95.5 ± 16.52x / min for group Ht 37-40%, and 112.89 ± 19.23x / min for group Ht <37%. Obtained an average increase of P frequency with decreasing Base Excess (BE) is 88.0 ± 0x / min for groups BE> 2, 92.33 ± 7.84x / min for BE Group 2 - (- 2), and 112.81 ± 19.22x / min for groups BE < -2. This means that there is a significant relationship between hematocrit decrease with increased of P frequency as one of the signs of hemorrhagic shock with p value = 0.046 and significant correlation between the decrease in BE with increased P frequency as one of the signs of hemorrhagic shock with p value = 0.028. Conclusion: There is a significant correlation between the value of the initial hematocrit and BE with signs of hemorrhagic shock due to intra-abdominal hemorrhage in patients with blunt abdominal trauma.